(untitled) (Indian Journal of Animal Production and Management, 2024)
Composting is the transformation of organic material through decomposition in to a biologically humus rich substance suitable for growing plants. The good management of those wastes would be an effective means of organic matter restoration through carbon restitution to the depleted soils through organic amendments. A properly managed composting process can destroy weed seeds, plant pathogens and human pathogens. The main goal of composting is carbon sequestration and enhances soil quality. Compost analysis assures buyers of bulk compost in addition to receiving good value for their money and safe organic fertilizer. Composting has four phases viz., mesophilic (21-45℃, thermophilic (45-68℃), mesophilic-II (<45℃) and maturation phase (Papale et al., 2021). The mesophilic phase also called hot phase, during which heterogeneous group of microorganisms were metabolically active and degrade the soluble compounds like sugars. The second phase is thermophilic phase/curing phase. Mesophilic organism was replaced by thermophilic organism and complex organic matter are degraded at this stage. High temperature in compost destroys the pathogenic organisms and contaminants. Composting is one of the methods used and among this forced aeration and turning method helps to improve the manurial value of compost. The present study is conducted to evaluate the effect of forced aeration and turning method in manurial value of cattle, goat and poultry manure compost.